#39: An 11-year Review of Lactobacillus Bacteremia at a Pediatric Tertiary Care Center. (28th June 2021) - Hefter, Yosefa; Powell, Lauren; Tabulov, Christine; Danan, Eleanor; Campos, Joseph; Hanisch, Benjamin
Abstract: Background: Probiotics are used frequently in the pediatric population for treatment of diarrhea and promotion of gastrointestinal health. Lactobacillus is the most commonly used bacterial genus in probiotic formulations. Lactobacillus spp. has been a reported cause of bacteremia, particularly in immunocompromised populations and individuals with impaired gut integrity. To assess the risks and benefits of inpatient probiotic use in a pediatric tertiary care center, we aimed to identify the occurrence of Lactobacillus bacteremia among hospitalized patients and its association with probiotic use over an eleven-year period. Methods: Cases of Lactobacillus bacteremia were identified through a search of positive blood culture reports from January 1 st, 2010 through December 31st, 2020. The clinical chart for each case was independently reviewed for the following risk factors: documented probiotic uses, presence of a central venous catheter, immunocompromising condition or immunosuppressive agent, neutropenia, impaired intestinal function and age below 3 months. Additionally, we reviewed the clinical presentation including presence of fever, need for intensive care and gastrointestinal symptoms. Total inpatient probiotic administration was assessed over the same time period. Results: Eight cases of Lactobacillus bacteremia were identified in inpatients during the study time period. Two cases had received probiotics in the hospital and a third case had documented outpatient administration of probiotics prior to development of bacteremia. The remaining five cases had no documented probiotic use. All 8 cases were febrile at the time of bacteremia. No patients required blood pressure support medications. Five cases had underlying impaired intestinal function. One case was in an oncology patient and there were no cases in solid organ or bone marrow transplant patients. Two cases, including the oncology patient and one patient with impaired intestinal function, were neutropenic at the time of bacteremia. All but one case, had a central line in place. All cases were treated with antibiotics and had resolution of bacteremia and associated symptoms. Probiotics were administered to 4, 478 inpatients during the study period. Conclusions: Lactobacillus bacteremia is uncommon and occurred in under 0.2% of patients who received probiotics during an inpatient admission. Nevertheless, all eight observed cases were symptomatic and received antibiotic therapy. Additionally, cases were most commonly seen in individuals with underlying impaired intestinal function. These considerations must be weighed in decisions regarding the risks and benefits of probiotic administration in the hospital.